New findings of Pleistocene fossil turtles (Geoemydidae, Kinosternidae and Chelydridae) from Santa Elena Province, Ecuador (2017)
New Pleistocene fossilized turtle remains from five localities of western Ecuador (Santa Elena Province) are described here. All these shell (carapace and plastron) fossil remains come from the Tablazo Formation and belong to three different lineages of cryptodires (“hidden-necked” turtles). The most abundant remains belong to geoemydids, attributed here to the genus Rhinoclemmys (indeterminate species). Less abundant in occurrence are the kinosternidids, attributed to Kinosternon (indeterminate species), and the first fossil record of chelydrids, Chelydra(indeterminate species), in the entirety of Central and South America.